(untitled) (Gestão & Regionalidade, 2017)
This study aims to assess the level of business’ maturity of textiles and clothing companies in the agreste of Pernambuco (Brazil), specifically in Santa Cruz do Capibaribe. Thus, competitiveness matrix diagnosis - proposed by the Fundação Nacional da Qualidade, following the guidelines of the Management Excellence Model - was applied. In this way, it was possible to perform a managerial diagnosis of the enterprises’ quality and sustainability. Case study methodology was used, with qualitative and quantitative approach, through the application of a questionnaire to 25 companies. It was through this instrument that the maturity degree and which items needed to be improved by the companies to stay in business while maintaining and/or increasing its market share were identified. The results suggest that, according to the average maturity degree, the analyzed enterprises are immature. In this case, they need to advance in the management and significantly improve its indicators.